Assessment of partial‐mouth periodontal examination protocols for periodontitis surveillance. (15th July 2014) - Tran, Duong T.; Gay, Isabel; Du, Xianglin L.; Fu, Yunxin; Bebermeyer, Richard D.; Neumann, Ana S.; Streckfus, Charles; Chan, Wenyaw; Walji, Muhammad F.
Abstract Objective To evaluate bias associated with nine identified partial‐mouth periodontal examination (PMPE) protocols in estimating periodontitis prevalence using the periodontitis case definition given by the Centers of Disease Control and Prevention and American Academy of Periodontology (CDC/AAP). Material and Methods Prevalence from full‐mouth examination was determined in a sample of 3667 adults ≥30 years old from the National Health and Nutrition Examination Survey (NHANES) 2009–2010. Prevalence, absolute bias, relative bias, sensitivity and inflation factor were derived for these protocols according to the CDC/AAP definition and half‐reduced CDC/AAP definition as ≤50% of sites were measured. Results Bias in moderate and severe periodontitis prevalence ranged between 11.1–52.5% and 27.1–76.3% for full‐mouth mesiobuccal‐distolingual protocol and half‐mouth mesiobuccal protocol respectively; according to the CDC/AAP definition. With half‐reduced CDC/AAP definition, half‐mouth four sites protocol provided small absolute bias (3.2%) and relative bias (9.3%) for the estimates of moderate periodontitis prevalence; corresponding biases for severe periodontitis were −1.2% and −10.2%. Conclusion Periodontitis prevalence can be estimated with limited bias when a half‐mouth four sites protocol and a half‐reduced CDC/AAP case definition are used in combination.